The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18632/aging.202285
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key modules and genes associated with breast cancer prognosis using WGCNA and ceRNA network analysis

Abstract: Breast cancer is one of the leading causes of cancer-associated mortality in women worldwide and has become a major public health problem. Although the definitive cause of breast cancer is not known, many genes sensitive to breast cancer have been detected using advanced technologies. Our study identified 3301 differentially expressed lncRNAs and mRNAs between tumor and normal samples from The Cancer Genome Atlas database. Based on the gene expression analysis and clinical traits as well as weighted gene co-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…WGCNA was run as described previously (22). Briefly, a similarity matrix was constructed using expression data and converted into an adjacency matrix, a ij .…”
Section: Wgcna Of Differential Tfsmentioning
confidence: 99%
See 1 more Smart Citation
“…WGCNA was run as described previously (22). Briefly, a similarity matrix was constructed using expression data and converted into an adjacency matrix, a ij .…”
Section: Wgcna Of Differential Tfsmentioning
confidence: 99%
“…In breast cancer, the novel microRNA biomarkers for each subtype of breast cancer can be detected using WGCNA (21). In addition, our previous study identified one lncRNA and five mRNA that serve as important prognostic biomarkers in breast cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“…Modular Significance (MS) and Gene Significance (GS) are used to calculate the expression patterns of modules related to disease traits. In this study, the dynamic tree cutting algorithm can be used to detect the module, and the minimum module size was 30 (20).…”
Section: The Weighted Gene Coexpression Networkmentioning
confidence: 99%
“… 4 WGCNA has been widely used for detecting disease biomarkers, and elucidating biological mechanisms and drug interactions. 5–7 Although biomarkers of HF have been identified, but due to heterogeneity of HF and its complicated pathophysiological manifestations, a single gene cannot accurately predict the characteristics of HF. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%